First description of a giant manta ray fetus Mobula birostris (Walbaum 1792) from Tumbes, Peru (Southeast Pacific) - Cabanillas-Torpoco, Mariano; Forsberg, Kerstin; Siccha-Ramírez, Raquel; Cisneros, Paola; Luque, Carlos; Purizaca, Wilmer; Asmat, Ray; Ampuero, Claudia; Rubin, Robert; Vera, Manuel (Zootaxa, 2019)
The population of Mobula birostris (“giant manta ray”) found in the waters of northern Peru and Ecuador is believed to be the largest in the world (Harding & Beirwagen, 2009). This species is considered to be the largest within the group of manta rays, as they attains at least 670 cm disc width (reported to 910 cm) (White et al., 2006) and there is a record of an individual weighing 2000 kg (Kunjipalu & Boopendranath, 1981). This species is ovoviviparous (matrotrophic viviparious) (Herbert, 2012). A single pup follows a gestation period of approximently one year, (Marshall et al., 2008, Mendonça et al., 2012). Sucessive pregnancies are speculated to be separated by a refactory period of two or more years (Mendonça et al., 2012). The objective of this study is to record the measurements of a M. birostris fetus of a female caught accidentally in the region of Tumbes, Peru. This is the first record of morphological and morphometric data regarding a manta fetus in Peru.